2021
DOI: 10.1371/journal.pone.0253138
|View full text |Cite
|
Sign up to set email alerts
|

Toe-brachial index is beyond a peripheral issue in patients with type 2 diabetes

Abstract: Background Atherosclerosis is the leading cause of death in patients with diabetes. We aimed to evaluate the association between ankle-brachial index (ABI) and toe-brachial index (TBI) with carotid intima-media thickness (CIMT) in patients with type 2 diabetes (T2DM). Methods This cross sectional study included 296 patients with T2DM who met the American Diabetes Association criteria for the assessment of peripheral arterial atherosclerosis. The ABI ≤ 0.9 and TBI ≤ 0.7 were considered as abnormal values. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The toe-brachial index, which provides a more accurate and sensitive risk evaluation than the ABI, especially in patients with diabetes, because it avoids underestimation of medial calcification of peripheral arteries [ 34 ]. The toe–brachial index may predict subtle carotid atherosclerosis [ 35 ] and also predict the risk of restenosis after angioplasty and stenting procedures [ 36 ]. Future studies to evaluate the association of the toe–brachial index and cerebral vessel diseases may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The toe-brachial index, which provides a more accurate and sensitive risk evaluation than the ABI, especially in patients with diabetes, because it avoids underestimation of medial calcification of peripheral arteries [ 34 ]. The toe–brachial index may predict subtle carotid atherosclerosis [ 35 ] and also predict the risk of restenosis after angioplasty and stenting procedures [ 36 ]. Future studies to evaluate the association of the toe–brachial index and cerebral vessel diseases may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that non-invasive testing such as Doppler and TBPI are more accurate and viable screening tests to identify PAD among patients with diabetes [31][32][33]. TBPI is often preferred for diagnostic testing because research has shown that this test provides a more accurate diagnosis in patients with diabetes with carotid atherosclerosis compared to ABPI [32,34,35]. The results of the interviews of this study indicated that the lack of podiatry consultation reimbursement and referral pathways hinders private podiatrists in Flanders, Belgium to invest in the equipment needed for noninvasive testing.…”
Section: Discussionmentioning
confidence: 99%
“…The normal values that those authors found were as follows: “young normal” 0.86 ± 0.03, “old normal” 0.91 ± 0.04, patients with diabetes mellitus (DM) 0.83 ± 0.04, coronary artery disease 0.87 ± 0.04, and hypertension 0.81 ± 0.03 [ 26 ]. Later, the cut-off value for TBI recommended for patients with DM and abnormally high ABI (>1.40) was 0.70 for TBI [ 4 , 27 ]. The study by Hyun et al set the range of normal TBI to 0.62–1.08 [ 13 ], which they suggested might have diluted the predictive value of TBI in their report.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present study’s data, the TBI corresponding to normal ABI was 0.711 (SD 0.173), which supports the normal TBI value found in recent guidelines [ 4 ]. However, the 0.10 discrepancy between normal values can be explained by a different approach compared to that used in the pioneering work of Carter and Lezack [ 4 , 26 , 27 ]. Recent guidelines and studies focus on the cut-off for a cardiovascular event and do not determine the normal value in subjects with no detectable PAD.…”
Section: Discussionmentioning
confidence: 99%